Contradictions Through the Lens of Activity Theory: Analyzing Discord as Online Collaborative Learning Platform - Awang Najib, Awang Mohamad; Zaimuariffudin Shukri, Nordin; Mohd Hafizan, Hashim (Contemporary Research Center CRC Publications, 2024)
The rapid integration of online platforms such as Discord into education has been studied from various perspectives but attempts to theorize the diverse and conflicting challenges faced by students learning through these platforms have been limited. This research adopted a qualitative approach to investigate students' experiences using Discord for online collaborative learning (OCL) at a matriculation college in Sarawak, Malaysia. Data obtained via text-based focus group interviews on Discord is presented in light of an Activity Theory (AT) framework. The finding identifies multiple contradictions in Discord's use: primary contradictions related to its high data and memory requirements, secondary contradictions between its design and user practices, tertiary contradictions between its current model and the need for new approaches, and quaternary contradictions with the broader educational system. These contradictions, categorized into dilemmas, conflicts, critical conflicts, and double binds, highlight the challenges in using Discord as an educational tool.. The research concludes with recommendations for developers, educators, and users to foster an environment that is both technologically robust and aligned with educational principles of accessibility and inclusivity.